How tubular aggregates interact with biomembranes: wrapping, fusion and pearling. Issue 2 (10th December 2015) - Yue, Tongtao; Xu, Yan; Sun, Mingbin; Zhang, Xianren; Huang, Fang
Abstract : How soft tubular aggregates interact with biomembranes is crucial for understanding the formation of membrane tubes connecting two eukaryotic cells, which are initially created from one cell and then connect with the other. Abstract : How soft tubular aggregates interact with biomembranes is crucial for understanding the formation of membrane tubes connecting two eukaryotic cells, which are initially created from one cell and then connect with the other. On the other hand, recent experiments have shown that tubular polymersomes display different cellular internalization kinetics in their biomedical applications compared with spherical ones with an underlying mechanism that is not fully understood. Inspired by above observations, in this work we investigate how tubular aggregates interact with biomembranes with the aid of computer simulation techniques. We identify three different pathways for membrane interaction with parallel tubes: membrane wrapping, tube-membrane fusion and tube pearling. For the first pathway, soft tubes can be wrapped from the top side by membranes through membrane monolayer protrusion, which cooperatively leads to a heterogeneous wrapping dynamics along with tube deformation. The second pathway found is that soft tubes fuse with the membrane under certain conditions. Both wrapping and fusion have distinct influence on the third pathway, tube pearling. While a weak membrane adhesion promotes tube pearling, the strong adhesion that leads to higher extent of membrane wrapping conversely restrains tube pearling. Under highly positive membrane tension, partial tube-membrane fusion provides another way to mediate tube pearling. The findings shed light on the formation of a bridge membrane tube and the rational design of tube-based therapeutic agents with improved efficiency for targeted cellular delivery.